2015
DOI: 10.1177/1550059414563306
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Asymmetries and Theta Activity in the Rostral Anterior Cingulate Cortex as EEG Signature of HIV-Related Depression

Abstract: Resting EEGs of 40 people living with HIV (PLWH) on long-term antiretroviral treatment were examined for z-scored deviations from a healthy control (normative database) to examine the main and interaction effects of depression and gender. Regions of interest were frontal (alpha) and central (all bands) for interhemispheric asymmetries in quantitative EEGs and theta in the rostral anterior cingulate cortex (rACC) in low-resolution electromagnetic tomography (LORETA). Z-scored normed deviations of depressed PLWH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…Moreover, in future studies, the potential influence of gender on the relationship between cortical asymmetry and empathy should be considered. Previous literature found that women in general show greater right-dominant frontal alpha asymmetry than men [39].…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, in future studies, the potential influence of gender on the relationship between cortical asymmetry and empathy should be considered. Previous literature found that women in general show greater right-dominant frontal alpha asymmetry than men [39].…”
Section: Discussionmentioning
confidence: 81%
“…Previous work has shown elevated activity within the sgACC to be a signature of depressive symptomology in HIV-infected individuals (Kremer, Lutz et al 2016). We expected that altered rsFC between the sgACC and regions of interest within the bilateral amygdala would correspond to the greater depressive symptomology in HIV+ participants.…”
Section: Discussionmentioning
confidence: 97%
“…Another potential limitation is the disproportionate number of males among the HIV+ participants. It is possible that the low number of females in this sample may have obscured some of the HIV-related findings, as gender effects have been observed for resting-state perigenual cingulate activity associated with depressive symptomology in HIV (Kremer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies have uncovered paucity in cortical activations associated with the decoding of affect in persons with higher levels of AL [132][133][134][135]. Because altered activity and volumetric reductions within brain structures associated with AL, such as anterior cingulate, are also observed in persons living with HIV [136] including those demonstrating an emotion recognition impairment [137] and patients with high negative affect [138], therapies that target cognitive and emotional functioning will are needed. Some of the more promising treatment options that may promote the mental representation of affect for persons with HIV may include Mentalization-based therapy [139] and Emotion Focused Therapy [140].…”
Section: Discussionmentioning
confidence: 99%